INVESTIGATION OF HYDROLOGICAL CAPACITY OF COFFEE PULP AND HYDROGEL AS BIOPORE FILLER IN RAIN GARDEN IN GREEN INFRASTRUCTURE, JALAN BARU HAMLET, NORTH SUMATRA - Waldemar Victoryno Simamora; Ikhwanudin; Muhammad Abrian Surya Putra; Salsabella Cantika Rahma Pangestika Putri Zaroh; Octavi Laila Kamaratih; Donny July Prasetyo (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2026)
Climate change and urbanization have increased surface runoff in Jalan Baru Hamlet, North Sumatra, due to low soil infiltration capabilities. This study aims to investigate the hydrological capacity of coffee pulp, hydrogel, and a combination of the two as biopore filler media in rain gardens as part of the implementation of green infrastructure. The experiment was carried out using five media variations, namely 100% hydrogel, 100% coffee pulp, and a combination of hydrogel–coffee pulp with a ratio of 75%:25%, 50%:50%, and 25%:75%. The parameters analyzed included water absorption rate and water absorption capacity at immersion times of 5, 10, and 15 minutes. The results showed that 100% hydrogel had the highest hydrological performance with an absorption rate of 40.34 g/g/min and an absorption capacity of 252.42 g/g. In contrast, 100% coffee pulp showed the lowest value with an absorption rate of 0.77 g/g/min and an absorption capacity of 5.15 g/g. Increasing the proportion of hydrogels in mixed media has been shown to significantly improve water absorption ability. The combination of 75% hydrogel: 25% coffee pulp produces an absorption capacity of 222.50 g/g, while the combination of 25%: 75% produces a capacity of 80.57 g/g. The combination of 50% hydrogel: 50% coffee pulp produces an absorption rate of 24.99 g/g/min and an absorption capacity of 134.48 g/g, and demonstrates the best balance between water retention, absorption stability, and ecological benefits. Coffee pulp plays a role in increasing the porosity of the medium and supporting the improvement of soil structure through the decomposition of organic matter, while hydrogel functions as a water retention medium with the ability to absorb and release water gradually. In addition to increasing water infiltration and retention capacity, the use of coffee pulp also supports the reduction of local organic waste and the application of circular economy principles. Thus, the combination of hydrogel–coffee pulp 50%: 50% is recommended as the optimal biopore filler medium for rain gardens because it has stable hydrological performance, is environmentally friendly, economical, and has the potential to support the sustainability of green infrastructure systems in controlling urban surface runoff.